Intestinal response to prolonged fasting and subsequent feeding in Mallard Anas platyrhynchos - Geiger, Sylvie; Wagner, Christel; Lignot, Jean-Hervé; Le Maho, Yvon; Robin, Jean-Patrice (Wildfowl, 2013)
In numerous species, prolonged fasting occurs during food shortage periods or when feeding competes with activities such as reproduction, migration or hibernation. Efficient energy saving, which is a key factor to adapt to this challenge, is partly achieved by an atrophy of the intestines. In this study, morphological and functional responses of the Mallard’s intestine during the metabolic phases of prolonged fasting (a phase of protein sparing followed by a phase of protein wasting) and subsequent feeding were determined. Morphometry of the intestinal villi and cell replication within intestinal crypts were examined. Prolonged fasting induced a significant (33%) atrophy of the villi but there were no changes in cell proliferation rate inside the crypts. These events are not phase-dependent, unlike in laboratory rats where cell proliferation is increased in the crypts during the protein wasting phase. Mallard do not rely on such mechanisms, but re-feeding remained successful. The absorption of nutrients in the jejunum seemed to be restored rapidly as the length of the villi increased by one-third and the proportion of cells in DNA synthesis increased by 70% within 24 h of subsequent feeding